T regulatory cells (TREG)(TCD4+CD25+FOXP3+) distribution in the different clinical forms of leprosy and reactional states - José Napoleão Tavares Parente; Carolina Talhari; Antônio Pedro Mendes Schettini; Cesare Massone (Sociedade Brasileira de Dermatologia, 2015)
BACKGROUND: Leprosy is characterized histologically by a spectrum of different granulomatous skin lesions, reflecting patients' immune responses to Mycobacterium leprae. Although CD4+CD25+ FoxP3+ T regulatory cells are pivotal in the immuneregulation, presence, frequency, and distribution of Tregs in leprosy, its reactional states have been investigated in few studies. OBJECTIVES: This study aimed to verify the frequency and distribution of regulatory T cells in different clinical forms and reactional states of leprosy. METHODS: We performed an immunohistochemical study on 96 leprosy cases [Indeterminate (I): 9 patients; tuberculoid tuberculoid: 13 patients; borderline tuberculoid: 26 patients; borderline borderline: 3 patients; borderline lepromatous: 8 patients; lepromatous lepromatous: 27 patients; reversal reaction: 8 patients; and erythema nodosum leprosum: 2 patients]. RESULTS: FoxP3-positive cells were present in 100% of the cases with an average density of 2.82% of the infiltrate. Their distribution was not related to granulomatous structures or special locations. There was a statistically significant increment of FoxP3 expression in patients with leprosy reversal reactions when compared with patients presenting with type I leprosy (P= 0.0228); borderline tuberculoid leprosy (P = 0.0351) and lepromatous leprosy (P = 0.0344). CONCLUSIONS: These findings suggest that Tregs play a relevant role in the etiopathogenesis of leprosy, mainly in type I leprosy reaction.